Steatosis affects chronic hepatitis C progression in a genotype specific way. (11th February 2004) - Rubbia-Brandt, L; Fabris, P; Paganin, S; Leandro, G; Male, P-J; Giostra, E; Carlotto, A; Bozzola, L; Smedile, A; Negro, F
Abstract : Background and aims: Liver steatosis is frequent in chronic hepatitis C, particularly in patients infected with hepatitis C virus (HCV) genotype 3. The aim of this study was to determine the relationship between steatosis and fibrosis in chronic hepatitis C as a function of viral genotype. Methods: A multivariable logistic regression analysis was carried out in 755 chronic hepatitis C patients (mean body mass index (BMI) 24.11 kg/m 2 ; 178 with genotype 3), consecutively admitted to three referral hospitals. Liver histology showed steatosis in 315 and fibrosis in 605 patients, of whom 187 had cirrhosis (78 compensated and 109 decompensated). Results: Steatosis was independently associated with fibrosis (p<0.001), genotype 3 (p<0.001), BMI (p<0.001), ongoing alcohol abuse (p<0.001), and age (p = 0.001). Fibrosis was associated with the Metavir activity score (p<0.001), age (p<0.001), steatosis (p = 0.001), past alcohol abuse for >5 years (p = 0.015), and BMI (p = 0.034). When regression analysis was repeated on patients divided according to viral genotype (that is, 3 v non-3) to identify type specific risk factors, steatosis was associated with ongoing alcohol abuse (p<0.001) and age (p = 0.01) only in non-3 genotype infected patients and with Metavir activity (p = 0.044) only in genotype 3 infected patients. Similarly, fibrosis was associated with steatosis only in genotype 3 infected individuals (p = 0.018), and with past alcohol abuse (p = 0.003) and (marginally) diabetes (p = 0.078) only in non-3 genotype infected patients. Conclusions: Steatosis influences chronic hepatitis C progression in a genotype specific way. Patients infected with genotype 3 and histologically confirmed steatosis should not be deferred from effective antiviral therapy.